Sistem Brankas Berbasis Internet Of Things Mengunakan Arduino Mega 2560 - Desnanjaya, I Gusti Made Ngurah (Prahasta Publisher, 2022)
Safes in the market are usually doesn’t offer a system that can monitor the activities carried out by users on the safe. This becomes a problem when the safe has many users who can access it. We can't identify who, when or what other users are doing. In addition, safes generally have an authentication system that only offers passcodes and keys. That authentication system is considered outdated. In this study, a web-based safe monitoring system was created that uses a fingerprint sensor and passcode as authentication. In addition, this system can also send data about user activity to the website so that admins or other users can monitor anyone who accesses the safe. This system will be tested using black box testing. In the test, it was found that this safe system can only be opened if the user inputs a valid passcode and a finger print that has been registered in the system. In addition, the activity data has been successfully sent to the website. In security testing, it was found that if the safe door is opened forcibly, an alarm in the form of a buzzer will ring and a warning notification will be sent to the website.